Waste Management Strategies by the Village Government: Strategi Pengelolaan Sampah oleh Pemerintah Desa - Achmadi, Ruri; Choiriyah, Ilmi Usrotin (Indonesian Journal of Law and Economics Review, 2024)
The general background waste management is a critical issue for sustainable community development, particularly in rural areas where resources are often constrained. Specific background in Wedoroklurak Village, effective waste management practices have become increasingly necessary due to rising waste production and its environmental impacts. Knowledge Gap: Although there is considerable literature on community-based waste management, there is limited research examining the specific roles of village governments in facilitating effective waste management strategies. Aims this study to analyze the roles of the village government in waste management, particularly its functions as a facilitator, mobilizer, and regulator. Results: The research findings reveal that the village government has successfully served as a facilitator by providing essential infrastructure, such as waste disposal facilities and educational resources for residents. Moreover, it has acted as a mobilizer by encouraging community participation through training programs. However, the government’s regulatory role has been inadequate, primarily relying on informal agreements rather than formal regulations. Novelty this study contributes valuable insights into the governance of waste management in rural contexts, emphasizing the need for more robust regulatory frameworks. Implications the findings suggest that strengthening regulatory measures can significantly improve waste management practices and promote sustainable environmental health in rural communities. Highlights: The government facilitates waste management through resource provision. Community education and training are essential for environmental awareness. Regulatory measures are needed for effective waste management practices. Keywords: Waste Management, Government, Community, Facilitator, Mobilizer